2006
DOI: 10.2337/dc06-0119
|View full text |Cite
|
Sign up to set email alerts
|

Iron Intake and the Risk of Type 2 Diabetes in Women

Abstract: OBJECTIVE -Epidemiological studies suggest that high body iron stores are associated with insulin resistance and type 2 diabetes. The aim of this study was to evaluate the association between dietary intake of iron and the risk of type 2 diabetes.RESEARCH DESIGN AND METHODS -We conducted a prospective cohort study within the Nurses' Health Study. We followed 85,031 healthy women aged 34 -59 years from 1980 to 2000. Dietary data were collected every 4 years, and data on medical history and lifestyle factors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
107
4
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 59 publications
10
107
4
3
Order By: Relevance
“…Repeated exposure assessments are important in cohort studies to reduce misclassification due to dietary changes during follow-up. In a cohort study the RR of type 2 diabetes was 1.28 for high vs low haem-iron intake (as a proxy for meat intake) when using cumulative updated averages of intake, but with only the baseline questionnaire the RR was weaker and not significant (RR 1.08) [39]. Four of the twelve included studies used repeated exposure assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated exposure assessments are important in cohort studies to reduce misclassification due to dietary changes during follow-up. In a cohort study the RR of type 2 diabetes was 1.28 for high vs low haem-iron intake (as a proxy for meat intake) when using cumulative updated averages of intake, but with only the baseline questionnaire the RR was weaker and not significant (RR 1.08) [39]. Four of the twelve included studies used repeated exposure assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Meat is an important source of total and saturated fat and could increase the risk of type 2 diabetes through overweight/obesity [41][42][43][44], the metabolic syndrome [45][46][47] and hyperinsulinaemia and hyperglycaemia [20, [48][49][50], although some studies found no association [51,52]. Another possible mechanism may be through the effects of haem-iron derived from meat [19,24,39,53]. Iron can promote oxidative stress by increasing the formation of hydroxyl radicals [54] which can cause damage to tissues, in particular the pancreatic beta cells [54].…”
Section: Discussionmentioning
confidence: 99%
“…In subjects without overt iron overload, higher serum ferritin levels are significantly associated with biochemical evidence of decreased insulin sensitivity (5,6). However, epidemiological studies of the association between dietary iron intake or biomarkers of tissue iron stores and the risk of diabetes in populations without overt iron overload have yielded mixed findings (5,6,(13)(14)(15)(16). The inconsistencies in these reports may be partly attributable to the presence of inflammation or other unmeasured confounders that alter the relationship between dietary iron intake, biochemical markers of tissue iron stores, and metabolic effects of iron.…”
Section: Figure 1-flow-mediated Dilation (Fmd In Low-frequency [Low Fmentioning
confidence: 98%
“…Diet plays an important role in both diseases (2,3) . While Fe deficiency may lead to anaemia (3) , findings from many countries show that high Fe intake, especially haem Fe intake (4) , and high body Fe stores increase the risk of diabetes (5)(6)(7) . Possible mechanisms for Fe increasing the risk of diabetes may include oxidative stress, inflammation, free fatty acid oxidation, insulin extraction and secretion (6) .…”
mentioning
confidence: 99%